Hydrogen pre-chamber combustion at lean-burn conditions on a heavy-duty diesel engine: A computational study. (1st March 2023) - Liu, Xinlei; Aljabri, Hammam; Silva, Mickael; AlRamadan, Abdullah S.; Ben Houidi, Moez; Cenker, Emre; Im, Hong G.
Highlights: Pure H2 pre-chamber combustion on a heavy-duty diesel engine was studied. The pathway to achieving highly efficient and clean combustion was explored. Active H2 pre-chamber combustion demonstrated a high knocking tendency. Ultra-low nitric oxide emissions were obtained at ultra-lean burn conditions. Over high compression ratio induced end-gas autoignition and limited load ranges. Abstract: The combustion of hydrogen generates almost no harmful emissions except for nitric oxides (NOx ), which could be effectively eliminated under lean-burn conditions. In particular, the pre-chamber combustion concept has the potential to further extend the lean-burn limit. To pursue a sustainable mode of the powertrain in future transportation, this work intended to investigate the hydrogen pre-chamber combustion concept on a heavy-duty diesel metal engine under lean-burn conditions. By using the CFD modeling method, the pathway to achieving higher engine efficiency along with lower NOx emissions were explored. The results demonstrated that the lean-burn passive pre-chamber combustion effectively restrained the heat release process within the pre-chamber and yielded negligible NOx emissions while degrading complete combustion and combustion stability as a trade-off. To extend the engine operating range, an adequate amount of fuel was introduced into the pre-chamber. Compared to methane, the active pre-chamber combustion of hydrogen exhibited a significantly higher tendency to induce end-gas autoignition owing to its faster heat release within the pre-chamber. The pressure rise rate within the pre-chamber was successfully controlled by adjusting the pre-chamber throat diameter. Higher thermal efficiency was achieved with an increased compression ratio at the same spark ignition timing because of the advanced combustion phasing. However, the operating range was narrowed for the limit of end-gas autoignition and high pressure rise rate.